Student's Acceptance of Computer-Aided Learning: An Empirical Investigation Using the Technology Acceptance Model (TAM) - Nozie Mazzuana, Md Arof (2011)
This quantitative project paper entitled Students’ Acceptance of Computer-Aided Learning: An Empirical Investigation Using the Technology Acceptance Model (TAM), aims to determine the effect of perceived ease of use (PE) and perceived usefulness (PU) as the independent variables on students’ attitude towards acceptance of the computer-aided learning as the dependent variable (ATT). This study also intends to examine whether any differences on the students’ attitude towards acceptance of the computer-aided learning (CAL) exist among the respondents from the urban and rural areas. Respondents for this study comprised 619 Form Four secondary schools students from the adjacent districts of Klang (urban) and Kuala Langat (rural) in Selangor. Three schools in Kuala Langat and four schools in Klang were selected randomly using random selection method of Microsoft Office Excel for the distribution of the questionnaires. Data were analyzed using SPSS version 17. Tests conducted were Pearson correlation,multiple regressions,T-test and One-way ANOVA. The Pearson correlation showed that PE and PU were correlated with ATT. The Pearson correlation result of PE to ATT was 0.75.The Pearson correlation result of PU to ATT was 0.710.Multiple regressions showed that PE and PU had significant effects on ATT. Without the mediator,the PE to ATT β-value was 0.750 for p < 0.01.The PU to ATT β-value was 0.504 with the same level of confidence. Perceived ease of use also had a significant effect on perceived usefulness.For the mediation effect,perceived usefulness mediated the relationship between perceived ease of use and students’ attitude towards acceptance of the CAL. With the mediation effect,the PE.PU to ATT β-value was 0.372 for p <0.01.This showed that PU was the partial mediator since the β-value was reduced and p-value was still p < 0.01.R2 changed significantly from 0.562 to 0.640 when PU was substituted.This also indicated that PU was the mediator. The finding of the T-test showed that there was a significant difference of students’ acceptance of the CAL between the rural and urban areas. Recommendations were suggested for the betterment of the educational system that are new policy enforcement,comprehensive training and skill development for teachers,and monitoring of the development and implementation of the CAL.